Cherenkov Emission Generated by a Modulated Source in 2D Dispersive Photonic Crystal Slabs. (26th February 2020) - Martínez-Sánchez, Erika; Burlak, Gennadiy; Rodríguez-Garcia, Carlos; Gallardo-Heredia, Marisol; Avila-López, Ulises
Abstract : This work presents a systematic numerical study of Cherenkov optical radiation generated by a modulated source that moves with uniform velocity on a two-dimensional (2D) photonic crystal (PCr) slab surface. We apply the FDTD technique with emphasis on the dispersion properties of the periodic medium to perform our numerical analysis. The field oscillations generated at the passage of a modulated source in the PCr produce a series of spectral resonances corresponding to the eigenmodes in the spatial frequency domain for the photonic slab. The amplitudes of the field oscillations have maximal values in the group cone closely to the path of the moving charge.